Analisis Perubahan Sistem Kerja Unit Airport Operational Control Center (AOCC) Pasca Pandemi Covid di Bandar Udara Internasional Pattimura Ambon - Sehat Wati Tomagola; Febriansyah Ignas Pradana (Lembaga Pengembangan Kinerja Dosen, 2023)
The covid-19 pandemic in Indonesia is part of the 2019 coronavirus disease (covid 19) pandemic that is currently taking place throughout the world. During the Covid 19 pandemic there was a system change at Pattimura Ambon Airport, especially in the AOCC unit, namely a change in online system services. The purposes of this study are 1) To determine the impact that the covid pandemic has had on performance at the Airport Operational Control Center (AOCC) unit. 2) To see the positive and negative values ​​due to the impact of the covid pandemic on the Airport Operational Control Center (AOCC) at Pattimura Ambon International Airport. This study uses a qualitative method. The instruments used were the researchers themselves supported by the results of interviews, observations and documentation with supporting documents from the AOCC and the air transport unit at Pattimura Ambon International Airport. To answer the formulation of the research problem, the researcher conducted 3 stages of analysis consisting of data reduction, data presentation, and drawing conclusions. The results of this study show that the Covid pandemic has had a huge impact on airport services because this pandemic has required the government to issue regulations that greatly impact AOCC service activities because it results in changes to the work system so that it also has an impact on the performance of AOCC service officers. This is also related to the solution set by the Airport Operational Control Center Unit, namely changing their work system in providing services to passengers. Previously, Customer Service Staff provided services to passengers directly, so during the pandemic this was changed through a monitor screen. Not only that, the Airport Operational Control Center Unit also changed the working hour limit which was originally until 08.00 Wit. during the pandemic, the limit of working hours for AOCC was only until 04.00 Wit. coupled with the change of staff every day alternately.